An Unpublished ‘Medallion’ of Elagabalus from Edessa in Osrhoene: Nergal and Syro-Mesopotamian Religious Continuity? - Dandrow, Edward (KOINON: The International Journal of Classical Numismatic Studies, 2021)
Following Elagabalus’ victory over Macrinus in June 218, the city of Edessa in Osrhoene issued a number of coins that celebrated and commemorated the ascension of the new emperor. On these early issues are symbols commonly found in the Greco-Roman iconographic lexicon (e.g., Nike, palm branch, and cornucopia).